Production of biodiesel and its application in engines - Shukla S.K.; Singh Rathore P.K. (My University, 2025)
The demand for energy has been increased manifold in the last decade because of the all-round development of mankind. A major portion of this energy is utilized by the transportation sector, which leads to a huge amount of greenhouse gas (GHG) emissions. Renewable sources of energy will play a crucial role to mitigate the effect of climate change caused due to emissions from the transportation sector. Biodiesel, because of its physical and chemical properties, can be used as a potential alternative and clean fuel for diesel engines. It is a renewable, nontoxic, eco-friendly, and sustainable alternative fuel for compression ignition engines. The present work consists of the production and the use of the biodiesel fuel obtained from various plants species to run the engine and to study the effects of biodiesel blends on the performance of the diesel engine. The effect of biodiesel on various performance parameters of the diesel engine has been reviewed. Additionally, Life-Cycle Assessment (LCA) and economic analysis of the biodiesel was also studied in order to analyze the overall cost required to develop the infrastructure for its growth and development. Since biodiesel production and technology related to its application in the engines are in the initial phase of the development in most of the countries. Therefore, a comparative analysis of various policy regulations implemented in various countries for the growth and development of the biodiesel and its application, was also carried out in the chapter. © 2020 Elsevier B.V. All rights reserved.